PENGELOLAAN KELEMBAGAAN BUMDes DALAM UPAYA MENINGKATKAN KEMANDIRIAN DAN KEBERLANJUTAN DESA - Moh. As’adi; Ansari (Institut Agama Islam Ngawi, 2022)
Abstract The independence and sustainability of BUMDes is part of the ideals of national development. As one of the economic institutions that operate in rural areas, BUMDes must have differences with economic institutions in general. This is intended so that the existence and performance of BUMDes is able to contribute significantly to the improvement of the welfare of villagers. The purpose of bumdes institutional management is to provide services for productive business, especially for rural poor groups, reduce the practice of rent and the release of money, create equitable effort, and increase the income of rural communities. As for this research, using qualitative research is a traditional understanding process based on methodological research of various social or human problems. While the data and data sources needed in this study are; primary data and skunder data. There are primary data, namely: 1) Focus group discussion (FGD), and discussions based on questions that have been prepared by researchers 2) Observation 3) Interviewing in depth, then the researcher analyzes the results of the interview. The results showed that the institutional management of BUMDes can improve village service standards, and must always be improved so that the improvement of independence, sustainability, and village defense can be achieved in accordance with the principles in the institutional management of BUMDes: 1) Cooperative, 2) Participatory, 3) Emancipatory, 4) Transparent, 5) Accountable, 6) Sustainable. Thus BUMDes can put forward the principle of gotong royong for rural communities to increase and accelerate rural economic growth. One of the main points is the support and supot of the village government in an effort to increase village independence in the pre-economic builder of the community. Keywords: Bumdes Management, Independence, Village Sustainability